1993
DOI: 10.1152/jappl.1993.75.6.2789
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and cardiovascular responses to static handgrip exercise in humans

Abstract: We studied the time course of respiratory and cardiovascular responses by evaluating changes in the breathing pattern, mean blood pressure (MBP), and heart rate elicited by 3 min of static handgrip at 15, 25, and 30% of the maximum voluntary contraction (MVC) in 15 healthy volunteers. Muscle tension and integrated electromyographic activity remained fairly constant during each trial. During 15% MVC bouts, initially only mean inspiratory flow increased; then, tidal volume and minute ventilation (VI) also rose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…In addition, there was no signi®cant relationship between peak D _ V I and peak BP during voluntary exercise and passive movement in either group. These results suggest that control of the blood pressure response is dierent from that of ventilatory and f c responses at the onset of exercise as has been suggested by Fontana et al (1993) andNo brega et al (1995). In this study, the BP in the children was increased a little or remained close to the rest value, while it was signi®cantly decreased in the adults during both voluntary exercise and passive movement.…”
Section: F C and Bp Responsessupporting
confidence: 69%
“…In addition, there was no signi®cant relationship between peak D _ V I and peak BP during voluntary exercise and passive movement in either group. These results suggest that control of the blood pressure response is dierent from that of ventilatory and f c responses at the onset of exercise as has been suggested by Fontana et al (1993) andNo brega et al (1995). In this study, the BP in the children was increased a little or remained close to the rest value, while it was signi®cantly decreased in the adults during both voluntary exercise and passive movement.…”
Section: F C and Bp Responsessupporting
confidence: 69%
“…6, significant correlations between aDV _ I and aDHR during brief voluntary exercise were recognized both in women (r=0.92, P<0.01) and in men (r=0.82, P<0.05), but not during brief passive movement. Fontana et al (1993) observed significant positive correlations between the increase in V _ I and that in HR during the final 30 s of 3 min of static handgrip exercises at 25% and 30% MVC but not at 15% MVC. Their study and the present study demonstrate that a relationship like this is observed not only during static exercise for a few minutes but also at the onset of voluntary exercise and that it is not recognized unless exercise over a certain intensity is performed.…”
Section: Gender Differencementioning
confidence: 78%
“…We have no information to explain this point. Nevertheless, Fontana et al (1993) suggest that the relationship between ventilatory response and HR response is caused by a considerable degree of coordination and integration of respiratory and cardiovascular functions at a central level, despite the possibility of a differential control. If so, it would be possible that this coordination and integration of respiratory and circulatory centers occurred to the same extent in women and men.…”
Section: Gender Differencementioning
confidence: 99%
“…Fontana et al (1993) have reported an increase in both respiratory frequency and tidal volume, whereas Muza et al (1983) have found no signi®cant changes in respiratory frequency during IHGE.…”
Section: Breathing Pattern and Pulmonary Ventilationmentioning
confidence: 95%